On the diffusion method of crystal growth - Lendvay, Ödön; Air Force Cambridge Research Laboratories (U.S.) (L.G. Hanscom Field, Bedford, Massachusetts : Air Force Cambridge Research Laboratories, Office of Aerospace Research, United States Air Force, 1969)
The simplest technical method for producing crystals of poorly soluble materials is diffusion growth. Through Diffusion growth nucleation processes may be limited or extended to chosen extent. The location and time of initiation for nucleation are directly calculable if the critical supersaturation or solubility product is known. The modification of nucleation time, duration, speed, time expansion, or contraction of extent may be achieved by simple methods. By the selection of experimental conditions different size distribution crystalline precipitates or macrocrystals may be produced. The latter may reach 1 cm size if system parameters are chosen correctly. The maximum dimensions of crystals produced are determined by the relationship of speed, nucleation, and growth. Largest dimensions through growth are usually exhibited by dendrites, twins, plain crystals, and needles. The so-called space crystals (where all three dimensions of the crystal are nearly equal) are generally smaller than the previous ones. The method has increased importance in cases where usual crystal growth methods may not be employed due ot the characteristics of the crystal to be produced.
Translation supported by the Air Force Cambridge Research Laboratories, Office of Aerospace Research, United States Air Force (L.G. Hanscom Field, Mass.), and translated by Transtek Associates, Reading, Massachusetts.
Translated from Magyar Fizikai Folyoirat, v. 8, no. 3, pp. 231-249, 1965.
AFCRL Research Library.
AD0692762 (from http://www.dtic.mil).
"June 1969."
Includes bibliographical references (page 25).
Keywords: Nucleation; Diffusion; Crystal growth; Nucleation; Diffusion; Crystal growth